Anti-Hypertensive Potential and Epigenetics of Angiotensin II type 2 Receptor (AT2R) - Chaudhary, Mayank (Current Hypertension Reviews, 2021)
Background: Renin angiotensin system (RAS) is a critical pathway involved in blood pressure regulation. Octapeptide, angiotensin II (Ang II), is a biologically active compound of RAS pathway which mediates its action by binding to either angiotensin II type 1 receptor (AT1R) or angiotensin II type 2 receptor (AT2R). Binding of Ang II to AT1R facilitates blood pressure regulation, whereas AT2R is primarily involved in wound healing and tissue remodeling. Objectives: Recent studies have highlighted the additional role of AT2R to counterbalance the detrimental effects of AT1R. Activation of angiotensin II type 2 receptor using AT2R agonist has shown the effect on natriuresis and release of nitric oxide. Additionally, AT2R activation has been found to inhibit angiotensin converting enzyme (ACE) and enhance angiotensin receptor blocker (ARB) activity. These findings highlight the potential of AT2R as a novel therapeutic target against hypertension. Conclusion: The potential role of AT2R highlights the importance of exploring additional mechanisms that might be crucial for AT2R expression. Epigenetic mechanisms, including DNA methylation and histone modification, have been explored vastly with relation to cancer, but the role of such mechanisms in the expression of AT2R has recently gained interest.
Keywords: angiotensin II type 2 receptor